Fault Classification Using Formal Modeling and Mutation Testing with Deep Learning - Kaddoura, Yara (2023)
A Master of Science thesis in Computer Engineering by Yara Kaddoura entitled, “Fault Classification Using Formal Modeling and Mutation Testing with Deep Learning”, submitted in January 2023. Thesis advisors are Dr. Khaled El-Fakih and Dr. Imran Zualkernan. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).